Quantities of total serum IgG antibodies against Circumsporozoite Protein among Postpartum Mothers attending Kawempe National Referral Hospital. A cross-sectional study. - Albert Olinga; Allan Lugaajju; Dr. Ivan Kimuli; Fatumah Namusoke (Student's Journal of Health Research Africa, 2026)
Background: The study aimed to determine the quantities of total serum IgG antibodies against CSP among Postpartum Mothers attending Kawempe National Referral Hospital. Methodology: A cross-sectional nested study was conducted using 194 archived serum samples randomly selected from 400 postpartum women who participated in a parent study at Kawempe National Referral Hospital. Samples stored at −80°C were analyzed at Makerere University College of Health Sciences Medical Biochemistry Laboratory. Anti-CSP IgG levels were quantified using ELISA, while IgG affinity was assessed using an ammonium thiocyanate avidity assay. Data were analyzed in Stata 14.2 using descriptive and inferential statistics, with statistical significance set at p≤0.05. Results: Among 194 postpartum mothers, 100.00% attended ANC; married/cohabiting mothers comprised 90.72%, while 9.28% were single/separated. With 51.03% having